RETRACTED ARTICLE: P16INK4a Deletion Ameliorated Renal Tubulointerstitial Injury in a Stress-induced Premature Senescence Model of Bmi-1 Deficiency - Jianliang Jin; Jianguo Tao; Xin Gu; Zhenzhen Yu; Rong Wang; Guoping Zuo; Qing Li; Xianhui Lv; Dengshun Miao (Scientific Reports)
Abstract To determine whether p16INK4a deletion ameliorated renal tubulointerstitial injury by inhibiting a senescence-associated secretory phenotype (SASP) in Bmi-1-deficient (Bmi-1−/−) mice, renal phenotypes were compared among 5-week-old Bmi-1 and p16INK4a double-knockout, and Bmi-1−/− and wild-type mice. Fifth-passage renal interstitial fibroblasts (RIFs) from the three groups were analyzed for senescence and proliferation. The effect of Bmi-1 deficiency on epithelial-to-mesenchymal transition (EMT) was examined in Bmi-1-knockdown human renal proximal tubular epithelial (HK2) cells, which were treated with concentrated conditioned medium (CM) from the fifth-passage renal interstitial fibroblasts (RIFs) of above three group mice or with exogenous TGF-β1. Our results demonstrated that p16INK4a deletion largely rescued renal aging phenotypes caused by Bmi-1 deficiency, including impaired renal structure and function, decreased proliferation, increased apoptosis, senescence and SASP, DNA damage, NF-κB and TGF-β1/Smad signal activation, inflammatory cell infiltration, and tubulointerstitial fibrosis and tubular atrophy. P16INK4a deletion also promoted proliferation, reduced senescence and SASP of RIFs and subsequently inhibited EMT of Bmi-1-knockdown HK2 cells. TGF-β1 further induced the EMT of Bmi-1-knockdown HK2 cells. Thus, p16INK4a positive senescent cells would be a therapeutic target for preventing renal tubulointerstitial injury.